Tumor Mouse Model Confirms MAGE-A3 Cancer Immunotherapeutic As an Efficient Inducer of Long-Lasting Anti-Tumoral Responses - Gérard, Catherine (Public Library of Science, 2014)
PURPOSE: MAGE-A3 is a potential target for immunotherapy due to its tumor-specific nature and expression in several tumor types. Clinical data on MAGE-A3 immunotherapy have raised many questions that can only be addressed by using animal models. In the present study, different aspects of the murine anti-tumor immune responses induced by a recombinant MAGE-A3 protein (recMAGE-A3) in combination with different immunostimulants (AS01, AS02, CpG7909 or AS15) were investigated. EXPERIMENTAL DESIGN AND RESULTS: Based on cytokine profile analyses and protection against challenge with MAGE-A3-expressing tumor, the combination recMAGE-A3+AS15 was selected for further experimental work, in particular to study the mechanisms of anti-tumor responses. By using MHC class I-, MHC class II-, perforin-, B-cell- and IFN-γ- knock-out mice and CD4(+) T cell-, CD8(+) T cell- and NK cell- depleted mice, we demonstrated that CD4(+) T cells and NK cells are the main anti-tumor effectors, and that IFN-γ is a major effector molecule. This mouse tumor model also established the need to repeat recMAGE-A3+AS15 injections to sustain efficient anti-tumor responses. Furthermore, our results indicated that the efficacy of tumor rejection by the elicited anti-MAGE-A3 responses depends on the proportion of tumor cells expressing MAGE-A3. CONCLUSIONS: The recMAGE-A3+AS15 cancer immunotherapy efficiently induced an antigen-specific, functional and long-lasting immune response able to recognize and eliminate MAGE-A3-expressing tumor cells up to several months after the last immunization in mice. The data highlighted the importance of the immunostimulant to induce a Th1-type immune response, as well as the key role played by IFN-γ, CD4(+) T cells and NK cells in the anti-tumoral effect.